Historia de los estudios paleornitológicos en el Museo de La Plata - Acosta Hospitaleche, Carolina Ileana Alicia (2022)
The first studies on fossil birds in the Museo de La Plata were carried out since the last decade of the 19th century. These were isolated studies, which did not increase their frequency or intensity until the beginning of the 20th century. Since then, an increasing amount and thematic deepening led to the specificity that today characterizes the scientific works around the world. From that moment, the Museo de La Plata was consolidated as a training center for paleontologists who established themselves in other institutions forming new work teams.